2017
DOI: 10.1111/jmwh.12657
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Type of Health Professional at Birth and Exclusive Breastfeeding

Abstract: Exclusive breastfeeding continuation may be influenced by the type of health professional attending the birth. In addition to having a skilled workforce, health care professionals involved in perinatal care need to be educated and trained to promote and support exclusive breastfeeding as recommended. The complex and multifactorial nature of the maternal decision to exclusively breastfeed requires broader understanding of contextual factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
1
16
1
Order By: Relevance
“…Researchers who conducted focus groups in rural and urban areas in Pakistan found that mothers and fathers believed that infants should first be fed prelacteal feedings by an elderly family member or a religious figure (Zakar et al, 2018). Studies have shown that the type of birth attendant is also associated with breastfeeding outcomes, with higher odds of exclusive breastfeeding among women cared for by traditional birth attendants (Hazir et al, 2013) and midwifes (Haile, Elmasry, Chavan, & Azulay Chertok, 2017;Wallenborn & Masho, 2018). The influence of these culturally designated advisers plays a critical role in the continuation of breastfeeding and lack of social support for breastfeeding contributes to low breastfeeding rates (Zakar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers who conducted focus groups in rural and urban areas in Pakistan found that mothers and fathers believed that infants should first be fed prelacteal feedings by an elderly family member or a religious figure (Zakar et al, 2018). Studies have shown that the type of birth attendant is also associated with breastfeeding outcomes, with higher odds of exclusive breastfeeding among women cared for by traditional birth attendants (Hazir et al, 2013) and midwifes (Haile, Elmasry, Chavan, & Azulay Chertok, 2017;Wallenborn & Masho, 2018). The influence of these culturally designated advisers plays a critical role in the continuation of breastfeeding and lack of social support for breastfeeding contributes to low breastfeeding rates (Zakar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-nine studies [16,60,[65][66][67]70,73,74,[76][77][78][79]83,86,88,89,[96][97][98][99][104][105][106][107][110][111][112]114,118]…”
Section: Study Characterisicsmentioning
confidence: 99%
“…However, a previous study from Lebanon reported a positive association between female gender of the pediatrician and breastfeeding for four months (OR = 1.49; 95% CI: 1.03 to 2.15) [21]. Moreover, a study reported the odds of EBF at three months to be higher among women whose birth was attended by a midwife or female nurse, as compared to birth by an obstetrician (OR = 1.87; 95% CI: 1.34 to 2.61) [22]. This may be because female obstetricians, who may have experienced motherhood and/or breastfeeding, would be more comfortable to address maternal concerns about infant nutrition, as compared to male obstetricians.…”
Section: Discussionmentioning
confidence: 99%